2013
DOI: 10.1055/s-0033-1334883
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Undercarboxylated and Reduced Carboxylated Osteocalcin are Associated with Metabolic Syndrome in Middle Age Asian Females

Abstract: Accumulating data suggest that bone plays a role in energy metabolism through decarboxylation of osteocalcin. Thus, we aimed to study the association of circulating under--carboxylated osteocalcin (UC-OCN) and car-boxylated osteocalcin (C-OCN) with metabolic syndrome in middle aged Asian population.In this cross-sectional study, 131 middle aged Asian subjects were recruited. Circulating UC-OCN, C-OCN and parameters of metabolic phenotype were measured.Circulating UC-OCN was increased in subjects with metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…While some studies found that undercarboxylated osteocalcin was correlated to energy metabolism, some did not 28. In one recent study in a female population, both carboxylated and undercarboxylated osteocalcin were associated with metabolic syndrome but the direction between the two associations was different 29. This study, as most of the other studies 11, 14, 15, 23, measured the total OC and did not differentiate the two forms.…”
Section: Discussionmentioning
confidence: 59%
“…While some studies found that undercarboxylated osteocalcin was correlated to energy metabolism, some did not 28. In one recent study in a female population, both carboxylated and undercarboxylated osteocalcin were associated with metabolic syndrome but the direction between the two associations was different 29. This study, as most of the other studies 11, 14, 15, 23, measured the total OC and did not differentiate the two forms.…”
Section: Discussionmentioning
confidence: 59%
“…Although some studies have linked ucOC levels to the risk of MetS through its relationship with individual cardiovascular risk factors 18,[40][41][42] ; to date, no studies evaluating the role of circulating ucOC as estimator of generalised cardiovascular risk in MetS patients are available. Our results show that ucOC serum levels could be an important estimator affecting cardiovascular risk expressed as CV-ZS, after adjusting by lifestyle and medication-related variables, only in those MetS patients who do not meet T2D criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that only the undercarboxylated part of serum OC was involved in the process of vascular calcification [ 21 ]. Recent studies suggested that uOC could serve as a novel biomarker for carotid atherosclerosis in patients with hypertension or metabolic syndrome [ 7 , 8 ]. The present study also demonstrated that uOC level was lower in CKD patients with carotid plaques and that uOC level inversely correlated with IMT, indicating that uOC might play a critical role in preventing carotid atherosclerosis and CVD in non-dialysis CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating total osteocalcin (tOC) is comprised of two major forms of OC, undercarboxylated osteocalcin (uOC) and carboxylated osteocalcin (cOC). Recent studies on patients with hypertension and metabolic syndromes have shown that uOC is closely associated with the development of CVD [ 7 , 8 ]. Alfadda et al measured the levels of all three forms of OC in patients with type 2 diabetes, and found that uOC was a better predictor of CVD risk in these patients than tOC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%